Vegetation communities and floristic diversity of eleyele and dandaru wetland in Ibadan, Southwest, Nigeria (2021)
Wetlands are globally important biodiversity hotspots and are facing rapid loss in floristic diversity and major changes in the functioning of these ecosystems due to various anthropogenic activities. However, wetlands located in large cities in developing nations are often unattended despite major yet often subtle changes in the functioning of the ecosystems. Recognizing this, the study was conducted in two wetland ecosystems, Eleyele and Dandaru wetlands in Ibadan city, southwestern Nigeria, to assess, document and determine the degradation or otherwise of the diversity and stand distribution of herbaceous and wood flora of the wetlands. The study was carried out on the wetlands of Eleyele (Lat, 7O25148.38″N, Long, 3O51145.18″E; elevation of 200 m ASL) in 2012. Systematic survey was carried out to assess the herbaceous and woody (girth ≥ 10 cm) components of the wetlands following Kent (2012) and Cox (1990) methods. Forty – five plotless sampling points of fifteen 5 m line transects, and twenty–one 10 m ×10 m plots were used for the respective surveys. Species presence and densities were used to compute Relative Importance Values and Diversity Indices following Kent (2012), Hammer et al. (2001) and Hill (1994). Topsoil was collected from the top 0 – 15 cm with a soil auger, bulked and analysed following AOAC (1984) methods. The wetland of Dandaru had higher diversity and was in a better floristic and edaphic health than Eleyele Lake wetland. This study recommends that Eleyele Lake wetland should be protected from anthropogenic activities that may lead to the loss of species.